2010
DOI: 10.1097/qai.0b013e3181f9c04c
|View full text |Cite
|
Sign up to set email alerts
|

HIV Among People Who Use Drugs: A Global Perspective of Populations at Risk

Abstract: This paper examines the epidemiology of HIV among selected subgroups of drug users around the world who are ‘most at risk’ - men who have sex with men (MSM), female sex workers (FSWs), prisoners, and mobile populations. The underlying determinants of HIV infection among these populations include stigma, physical and sexual violence, mental illness, social marginalization, and economic vulnerability. HIV interventions must reach beyond specific risk groups and individuals to address the micro- and macro- level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 90 publications
1
29
0
Order By: Relevance
“…Among HIV-positive SW, 52.2% ever injected drugs. This is consistent with research demonstrating that HIV infection is driven largely by the overlap of injecting drug use and sex work 10 11 21. Our study also found a higher proportion of injecting drug users working outdoors which heightens vulnerability to HIV infection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among HIV-positive SW, 52.2% ever injected drugs. This is consistent with research demonstrating that HIV infection is driven largely by the overlap of injecting drug use and sex work 10 11 21. Our study also found a higher proportion of injecting drug users working outdoors which heightens vulnerability to HIV infection.…”
Section: Discussionsupporting
confidence: 92%
“…Increased risk of HIV infection can result from multiple exposures: large number and concurrency of sexual partners, inconsistent condom use,7 8 intersection with injecting drug use9 10 and presence of other sexually transmitted infections (STIs) 7 11. In addition, among SW, infection risk and the adoption of unsafe behaviours vary across economic strata, sociocultural context and work environments 12.…”
Section: Introductionmentioning
confidence: 99%
“…FSW-IDUs face a number of vulnerabilities including entrenched poverty, mental illness, violence from clients or intimate partners, and conflict with sex partners surrounding drug use. These factors may directly or indirectly impair FSWs’ ability to negotiate male condom use and thus increase their risk of STIs [2729]. Furthermore, compared to non-IDU female sex workers, FSW-IDUs may also be more likely to acquiesce to clients’ demands for unprotected sex if they are suffering from drug-related withdrawal [24].…”
Section: Introductionmentioning
confidence: 99%
“…The articles by Beyrer et9 and by Stockman and Strathdee10 point to the rapidly changing epidemiology of HIV and drug abuse around the world. In Afghanistan, as in countries in Central Asia, the Commonwealth of Independent States, and in Africa, opium supplies are plentiful, leading to increases in heroin use, addiction, and the unsafe use of syringes and other equipment for drug injection.…”
mentioning
confidence: 99%